The Implementation of Jemparingan Games in Kulon Progo Regency, Yogyakarta (A Case Study at Pembina Wates State Kindergarten) - Islammeiliani, Dinna; Dewanti Handayani, Sri Sularti; Aeni, Kurotul (Universitas Negeri Semarang, 2021)
Jemparingan is a traditional Mataram style archery sport activity typical Yogyakarta Palace. This study intends to analyze the implementation of Jemparingan sport and its benefits in early childhood. The place of the research is Pembina Wates State Kindergarten, Kulon Progo Regency, Yogyakarta. The method of this research is a qualitative case study approach. The subjects are children in grades A and B. Data collection techniques are observation, interview, and documentation. For data analysis was used Miles and Huberman theory, namely data reduction, data presentation, and conclusions. The results of this study were the Jemparingan game as a play and learning activity in Pembina Wates State Kindergarten, which effectively trained children's focus, fine motor skills; train focus of the eye; increase concentration; confident; and build the character of the child in the kindergarten from an early age. The conclusion of this research is Jemparingan sport can be a fun game, effectively increasing child’s skill, and introducing Yogyakarta's local culture to children from an early age.